Comparing emergy accounting with well-known sustainability metrics: The case of Southern Cone Common Market, Mercosur - Giannetti, B. F.; Almeida, C. M. V. B.; Bonilla, S. H. (Elsevier B.V., 2010)
The quality and the power of human activities affect the external environment in different ways that can be measured and evaluated by means of several approaches and indicators. While the scientific community has been publishing several proposals for sustainable development indicators, there is still no consensus regarding the best approach to the use of these indicators and their reliability to measure sustainability. It is important, therefore, to question the effectiveness of sustainable development indicators in an effort to continue in the search for sustainability. This paper compares the results obtained with emergy accounting with five global Sustainability Metrics (SMs) proposed in the literature to verify if metrics are communicating coherent and similar information to guide decision makers towards sustainable development. Results obtained using emergy indices are discussed with the aid of emergy ternary diagrams. Metrics are confronted with emergy results, and the degree of variability among them is analyzed using a correlation matrix created for the Mercosur nations. The contrast of results clearly shows that metrics arrive at different interpretations about the sustainability of the nations studied, but also that some metrics may be grouped and used more prudently. Mercosur is presented as a case study to highlight and explain the discrepancies and similarities among Sustainability Metrics, and to expose the extent of emergy accounting. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: sustainability indices; Mercosur; Energy